Klasifikasi Gejala Awal Covid-19 dengan Algoritma Classification and Regression Tree (Cart) - Alamsyah, Agung; Desiani, Anita; Cahyono, Endro Setyo (Universitas Muhammadiyah Ponorogo, 2023)
COVID-19 is a disease that can cause death and can spread to others. By identifying early symptoms of the disease, early detection can be made for several symptoms that may cause COVID-19. One way to predict COVID-19 is through classification methods. By identifying the symptoms that have an impact on COVID-19, it is hoped that the COVID-19 virus can be stopped from spreading and the world's condition can be normal. This study shows an analysis of attributes that may have an impact on the onset of COVID-19 in an individual. The classification method used is one of the decision tree methods, namely the Classification and Regression Tree (CART). The training and testing methods used in this study are cross-validation and percentage split. The attribute that has a significant influence in this classification using CART method is lung infection. The performance of the system using cross-validation method with a value of k of 10 obtained an accuracy of 85%, which is considered good, while using a percentage split of 66%, an accuracy of 87% was obtained. The evaluation results for the class indicating COVID-19 with precision and recall in cross-validation are 70% and 68%, respectively, while for the percentage split method, precision and recall values of 75% and 70% were obtained, respectively.